KOREKTOR FAKTOR DAYA OTOMATIS PADA INSTALASI LISTRIK RUMAH TANGGA - Yuniarto, Yuniarto; Ariyanto, Eko (Vocational School Diponegoro University, 2018)
TL lamps, electric motors, Air Conditioner (AC), and other electrical equipment which is widely used for industry and households. Where all the electrical equipment is a burden that is inductive. As a result of the use of an inductive load, causing the falling value of the electrical power factor mounted on the customer can not be used optimally. To overcome this, in this thesis, has created a tool to correct the power factor value automatically. To improve the power factor, is used capacitors mounted in parallel to the load. By using the integrator, it can be obtained how large capacitor must be mounted parallel to the load according to the inductive load changes resulting in improved power factor value. Test results showed that an increase in the value of power factor from 0.34 to 0.95.